Screening evidence and practice - Raffle, Angela E.; Gray, J. A. Muir (John Armstrong Muir) (Oxford : Oxford University Press, 2007)
Screening is the routine testing of populations to identify individuals who may have a particular medical condition or disease. This book covers the theory and evidence behind screening, and serves as a practical, non-technical introduction to the subject, for public health practitioners involved in all aspects of screening.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical screening